A comparison between medication reconciliation by a pharmacy technician and the use of an online personal health record by patients for identifying medication discrepancies in patients' drug lists prior to elective admissions. (March 2021) - van der Nat, Denise J.; Taks, Margot; Huiskes, Victor J.B.; van den Bemt, Bart J.F.; van Onzenoort, Hein A.W.
Highlights: Medication reconciliation (MR) is time consuming and its success relies on the quality of different information sources. Online personalized health records (PHRs) increase patient empowerment and may overcome the implementation problems of MR. Patients who used an online PHR can relatively accurately record a list of their medication. PHRs may have the potential to replace MR in detecting medication discrepancies. Abstract: Aim: Medication discrepancies (MDs), defined as unexplained differences among medication regimens, cause important public health problems with clinical and economic consequences. Medication reconciliation (MR) reduces the risk of MDs, but is time consuming and its success relies on the quality of different information sources. Online personalized health records (PHRs) may overcome these drawbacks. Therefore, the aim of this study is to determine the level of agreement of identified MDs between traditional MR and an online PHR and the correctness of the identified MDs with a PHR. Methods: A prospective cohort study was conducted at the cardiology, neurology, internal medicine and pulmonary department of the Amphia Hospital, the Netherlands. Two weeks prior to a planned admission all patients received an invitation from a PHR to update their medication file derived from the Nationwide Medication Record System (NMRS). At admission MR was performed with all by a pharmacy technician, who created the best possible medication history (BPMH) based on the NMRS data and an interview. MDs were determined as discrepancies between the available information from the NMRS and the input and alterations patients or pharmacy technician made. The number, correctness of patients' alterations, type and severity of identified MDs were analysed. Results: Of 488 patients approached, 155 (31.8 %) patients who both used the PHR and had received MR were included. The mean number of MDs identified with MR and PHR was 6.2 (SD 4.3) and 4.7 (SD 3.7), respectively. 82.1 % of the drug information noted by the patient in the PHR was correct compared to the BPMH and 98.6 % had no clinically relevant differences between the lists. Conclusion: Patients who used an online PHR can relatively accurately record a list of their medication. Further research is required to explore the level of agreement and the correctness of a PHR in other (larger) hospital(departments).